Pendampingan Edukasi Manajemen UMKM yang di Kelola Perempuan Berbasis Digital - Hafidah, Andi; Idrus, Imriani; S, Sartika; Ramli, Risnawati (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Data shows that many MSMEs in Indonesia are managed by women, which creates economic opportunities and improves families' living standards.  The digital era is a business opportunity for entrepreneurs to take advantage of.  One of the goals of this service activity is to strengthen the role of women in the economy by providing the tools and knowledge needed to be successful in the business world.  The method used is in the form of Participation Action Research (PAR), with a participatory approach, then implemented into an action, education, presentation model and discussion/question and answer.  The results of the service activities show that there are already 2 cadres who have succeeded in starting a business and this has become a motivation for the others Post test and pre test results data on interest in entrepreneurship showed a significant increase in interest from 22.7% to 81.8% and post test and pre test results on knowledge also increased from 45.5% to 77.3%.  Conclusion: digital-based management education for MSMEs managed by women is very important and needs attention because the community, especially women, especially posyandu cadres in Parang Tambung  Village, are very interested in entrepreneurship but still lack skills in using digital technology or social media as a platform for marketing and promoting products.   Therefore, the cadres remain enthusiastic to help and motivate their members so they can take business opportunities to improve family welfare.